Simplify (x-2)^2

4 Answers | Add Yours

sciencesolve's profile pic

sciencesolve | Teacher | (Level 3) Educator Emeritus

Posted on

You need to expand the binomial using the formula `(a-b)^2 = a^2 - 2ab + b^2` .

Hence, substituting x for a and 2 for b yields:

`(x - 2)^2 = x^2 - 4x + 4`

You may also use distributive multiplication such that:

`(x - 2)^2 = (x - 2)(x - 2) = (x-2)*x +(x-2)*(-2)`

Opening the brackets yields:

`(x - 2)^2 = x*x - 2*x + x*(-2) - 2*(-2)`

`(x - 2)^2 = x^2 - 2x - 2x + 4`

`(x - 2)^2 = x^2 - 4x + 4`

Hence, expanding the binomial `(x-2)^2`  yields `(x - 2)^2 = x^2 - 4x + 4.`

winsorburnell's profile pic

winsorburnell | Student, Undergraduate | eNotes Newbie

Posted on

It's simple quadratic equationYou can used the formula of (a-b) the whole square.you have to just factorized the equation.luxury vacation bali

We’ve answered 315,604 questions. We can answer yours, too.

Ask a question